The Development of Geographic Information System for the Elderly Healthcare Management in Thailand - Thojampa, Somsak; Boonpracom, Roongtiva; Chidburee, Polpreecha (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to develop the elderly’s health database by applying the Geographic Information System (GIS). The sample of this research is carried out on people aged 60 years and over with 1,023 elderly people, five healthcare professionals, two chiefs of the village, and 30 health volunteers in the studied area. The necessary data for this research are as follows: 1) The elderly population data in the area which consisted of the locations of the elderly’s accommodations, data concerning the elderly’s health, and other general information such as age, profession, etc.; 2) the creation of a database system in terms of applying GIS, which is the use of spatial data from the offline database, in order to develop the elderly health mapping; 3) the utilization of the online database through the website in order to be applied as a guideline for the elderly healthcare management in the studied area. The results of this research are as follows: 1) the health mapping for the elderly in Tambon Nong Phra, Wang Thong District, Province of Phitsanulok classified by the set of data from both online and offline systems. The mentioned database was presented by visualization in order to make it possible to interpret the map instead of reading from a data statistics table. The data can also be always updated. 2) The results can be a guideline for Nong Phra Health Promoting Hospital in Wang Thong District, Province of Phitsanulok to utilize the developed database for the purpose of the elderly’s healthcare management in the mentioned area.